2020
DOI: 10.48550/arxiv.2005.08995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observing Correlations Between Dark Matter Accretion and Galaxy Growth: I. Recent Star Formation Activity in Isolated Milky Way-Mass Galaxies

Christine O'Donnell,
Peter Behroozi,
Surhud More

Abstract: The correlation between fresh gas accretion onto haloes and galaxy star formation is critical to understanding galaxy formation. Different theoretical models have predicted different correlation strengths between halo accretion rates and galaxy star formation rates, ranging from strong positive correlations to little or no correlation. Here, we present a technique to observationally measure this correlation strength for isolated Milky Way-mass galaxies with z < 0.123. This technique is based on correlations be… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Although these fitting functions where obtained in [13] at fixed Γ, subsequent studies have shown that they evolve with redshift [16]. This is most likely due to the physics of mass accretion, which dominates mass growth at very high redshift [51][52][53][54]. Thus, we parametrise Γ as Γ(z) = Γ 1 + Γ 2 z.…”
Section: Dependence Of Hi Statistics On Splashback Radiusmentioning
confidence: 99%
“…Although these fitting functions where obtained in [13] at fixed Γ, subsequent studies have shown that they evolve with redshift [16]. This is most likely due to the physics of mass accretion, which dominates mass growth at very high redshift [51][52][53][54]. Thus, we parametrise Γ as Γ(z) = Γ 1 + Γ 2 z.…”
Section: Dependence Of Hi Statistics On Splashback Radiusmentioning
confidence: 99%
“…One scenario could be that the more massive halo has a larger gravitational potential and is able to cool hot accreted gas more efficiently for steady star formation, presented as the "hot-mode" accretion in Katz et al (2003) and Kereš et al (2005) or recycle earlier accreted hot gas easier (e.g. O'Donnell et al 2020). A second scenario could be that higher mass haloes contain more satellites, which could supply gas to their centrals via interactions and mergers in order to sustain their star formation (e.g.…”
Section: Trends In the Formation Timesmentioning
confidence: 99%
“…This, in turn, influences the formation of clusters and luminous galaxies. From a galaxy formation perspective, many recent studies have confirmed that MAR correlates with star formation and is therefore valuable in probing galaxy growth ★ E-mail: exhakaj@ucsc.edu (e.g., Diemer et al 2013;Wetzel & Nagai 2015;O'Donnell et al 2020).…”
Section: Introductionmentioning
confidence: 99%